Twelve tips for efficient procedural simulation. (3rd July 2018) - Rivière, Etienne; Saucier, Danielle; Lafleur, Alexandre; Lacasse, Miriam; Chiniara, Gilles
Abstract: Procedural simulation (PS) is increasingly being used worldwide in healthcare for training caregivers in psychomotor competencies. It has been demonstrated to improve learners' confidence and competence in technical procedures, with consequent positive impacts on patient outcomes and safety. Several frameworks can guide healthcare educators in using PS as an educational tool. However, no theory-informed practical framework exists to guide them in including PS in their training programs. We present 12 practical tips for efficient PS training that translates educational concepts from theory to practice, based on the existing literature. In doing this, we aim to help healthcare educators to adequately incorporate and use PS both for optimal learning and for transfer into professional practice.